ANALYSIS OF EVENT-RELATED POTENTIALS OF EEG SIGNAL USING DISCRETE WAVELET TRANSFORM - Krotkikh, S. S.; Kirichenko, L. O. (Radio Electronics, Computer Science, Control, 2012)
In this work we use discrete wavelet transform for analyzes the frequency structure of EEG signal with evoked potentials after effect of stimulus. The method for determining the response time to a stimulus, based on the evaluation of the wavelet entropy and relative wavelet entropy EEG, has been implemented.